Possessed: A History of Law & Justice in the Crown Colony of Lagos (1861-1906) - Shasore, Olasupo (Quramo Publishing Ltd, 2014)
This is a new and revealing view of hidden accounts, court evidence, testimony and papers of enquiry showing how colonisation employed ''law and justice'' to achieve its pernicious objectives - changing the course and African society. This book assist with a clear picture of the special status of Lagos in the creation of our country. It sets the scene of a bitter battle fought by the people of Lagos to resist conquest by foreigners and presents a more accurate view of the infamous but false giving-away of Lagos by one of its rulers. It even gives us a sense of the lack of certainty in the mind of the colonisers as to how to execute the plan of possession...
Keywords: Colony of Lagos; History; Non-Fiction